Tuber aestivum Vittad. mycelium quantified: advantages and limitations of a qPCR approach - Gryndler, Milan; Trilčová, Jana; Hršelová, Hana; Streiblová, Eva; Gryndlerová, Hana; Jansa, Jan (Mycorrhiza, 2013)
A quantitative real-time PCR (qPCR) marker Ta0 with hydrolysis probe ("TaqMan"), targeted to the internal transcribed spacer region of the ribosomal DNA, has been developed for quantification of summer truffle (Tuber aestivum) mycelium. Gene copy concentrations determined by the qPCR were calibrated against pure culture mycelium of T. aestivum, enabling quantification of the mycelium in soil and in host roots from the fields. Significant concentrations of the fungus were observed not only in the finest roots with ectomycorrhizae but also in other root types, indicating that the fungus is an important component of the microbial film at the root surface. The concentration of T. aestivum in soil is relatively high compared to other ectomycorrhizal fungi. To evaluate the reliability of the measurement of the soil mycelium density using qPCR, the steady basal extracellular concentration of the stabilized T. aestivum DNA should be known and taken into account. Therefore, we addressed the stability of the qPCR signal in soil subjected to different treatments. After the field soil was sieved, regardless of whether it was dried/rewetted or not, the T. aestivum DNA was quickly decomposed. It took just about 4 days to reach a steady concentration. This represents a conserved pool of T. aestivum DNA and determines detection limit of the qPCR quantification in our case. When the soil was autoclaved and recolonized by saprotrophic microorganisms, this conserved DNA pool was eliminated and the soil became free of T. aestivum DNA.
Keywords: Mycelium; kořeny rostlin; Ascomycota; mycelium; Soil Microbiology; Mycorrhizae; mykorhiza; Real-Time Polymerase Chain Reaction; Plant Roots; půdní mikrobiologie; DNA, Fungal; kvantitativní polymerázová řetězová reakce; DNA fungální